(untitled) (Economics and region, 2022)
Ecocultural tourism, a new type of tourism brought about by the relationship between cultural and nature tourism, aims to develop cultural and ecological resources by presenting the ecological and cultural components of the landscape together. Sustainability and participation are two key factors crucial to the long-term future of tourism. Appropriate strategies should be defined to realize the potential of ecotourism, which carries all the principles of sustainability, and ecocultural tourism, where nature is valued together. Within the framework of these strategies, the concept of "eco-museum" that preserves the natural and cultural environment as a whole comes to the fore in international practice. The joint use of eco-cultural heritage in the liberated territories allows for the creation of this strategy. In particular, the wide potential of territories freed from occupation for the use of cultural and natural heritage creates favorable conditions for the development of eco-cultural tourism. It creates favorable conditions for the organization of eco-cultural, ethno-cultural, eco-health and eco-ethno-cultural tourism clusters in the liberated territories, which is based on the rich natural and cultural heritage potential of the region. Tugh-Azıx-Tağlar in Khojavand region, Zulfugar village and its surroundings in Kalbajar region, Shusha city and Dashalti village, Minkend in Lachin region and nearby examples of cultural heritage allow the formation of eco-ethno-cultural tourism clusters. It should also be noted that the settlements and ancient graves found as a result of archaeological excavations in Aghdam region, the areas around Shahbulag create conditions for the formation of an eco-cultural tourism cluster. At the same time, joint use of natural and cultural heritage in territories freed from occupation, restoration of the infrastructure of the clusters to be formed, and establishment of new communication links increase the prospects of its use. At the same time, the article analyzes the possibilities of using the natural, tangible and intangible heritage potential of the liberated regions from the point of view of ecotourism, the spread of existing resources, their importance in terms of eco-cultural tourism, the possibilities of joint use with other types of tourism, and the role in ensuring the employment of the population in the future settlement. is done. At the same time, regions favorable for the development of eco-cultural and eco-health tourism are analyzed and directions for the formation of clusters in this area are indicated.